COMPARATIVE IMMUNE RESPONSES OF CHILDREN AFTER INTRADERMAL AND INTRAMUSCULAR RABIES VACCINATION - Subawa, A. A. Ngurah; Sutirta Yasa, I Wayan Putu; Astawa, Nyoman Mantik (BALI MEDICAL JOURNAL; Vol 3 No 3 (2014), 2014)
Background: Rabies is a cause of death to people within 100% of Case Fatality Rate. Approximately  55.000 people died because of rabies each year, the vast majority of these deaths happen in Asia and  Africa. This study aims to find out comparative immune responses of intradermal (ID) and  intramuscular (IM) vaccination in children. Method: This was an experimental study to determine  antibody response of ID and IM rabies vaccines with randomized pre and posttest control group  design. ID and IM vaccination were carried out in 4 replication for each group. A number of 16  children were recruited for each group. Enzyme Linked Immunosorbent Assay (ELISA) was applied  to determine titers antibody on day 0, 7, 21, and 28 after vaccination. Results: This study found that  titer antibody induced by ID vaccination was lower than IM vaccination. However, the different is not  statistically significant in both groups  ( p > 0.05). Titers antibody on day 7 after vaccination were 3.08  ± 2.09 IU/ml intradermally and 4.22 ± 3.02 IU/ml intramuscularly. On day 21 and 28 after intradermal  vaccination, titers antibody were 6.78 ± 3.52 IU/ml and 12.53 ± 5.92 IU/ml, respectively.  Intramuscularly, antibody titers were 9.76 ± 4.86 IU/ml on day 21 and 14.98 ± 7.76 IU/ml on day 28.  Conclusion: ID vaccination is safe and can be used as an alternative vaccination for rabies in human.  In addition, 0, 7, 21 ID vaccination methods can be recommended for use to control rabies cases in  Indonesia because that methods induce protective immune response.
Keywords: Antibody, titer, Antirabies, vaccine, immune response.